A Systematic Review of Solid Waste Management in Indonesia: Generation, Characteristics, Treatment, and Regulation - Abdul Hakim Zakkiy Fasya; Mursyidul Ibad; Kuuni Ulfah Naila El Muna; Shofi Futri Pratiwi; Shofiyah Ajeng Sekar Arum (Universitas Airlangga, 2025)
Introduction: Research on solid waste in Indonesia remains relatively fragmented, with many studies still focusing on the development of solid waste management in urban areas. This study seeks to address the information gap by reviewing the development of solid waste management in Indonesia. Discussion: This systematic review was conducted through literature searches in Scopus, PubMed, and Google Scholar, selecting 38 articles that specifically examined solid waste in Indonesia in terms of its generation, characteristics, management, and regulatory frameworks. Collective evidence showed that household waste generation in Indonesia is strongly influenced by various factors such as income level, residential location, season, and public awareness of waste management. Waste banks and the 3R approach are the main pillars of community-based strategies, with composting applied to organic waste. Waste processing facilities play a supporting role within the community, such as WTE and incineration. Landfills remain necessary as a final solution for residual waste that cannot be further processed. Law No. 18 of 2008 on Waste Management serves as the primary regulatory framework in Indonesia. This law shifts the traditional paradigm of